Structural and dielectric properties of POSS reinforced polyimide nanocomposites - BİRTANE, HATİCE; ESMER, KADİR; KAHRAMAN, MEMET VEZİR; MADAKBAŞ, SEYFULLAH (TAYLOR & FRANCIS INC, 2019)
In this study, a series of [3-(2-aminoethyl)amino]propyl-heptaisobutyl substituted polyhedral oligomeric silsesquioxane (AHIP) containing polyimide (PI) nanocomposites were successfully prepared. Structural, thermal and electrical properties of the polyimide nanocomposites were studied. The properties of AHIP containing polyimides were compared with those of the neat polyimide films. The surface morphology of the prepared AHIP containing polyimides were determined by using Scanning Electron Microscopy (SEM). The hydrophilic/hydrophobic nature of AHIP/polyimide composites were analyzed by measuring their water contact angles. It was found that the addition of AHIP into the polyimide slightly increased the contact angle values. The incorporation of 5% AHIP to the PI matrix decreased the dielectric constant value of pure PI from 8.6 to 11.7, respectively. Furthermore he dielectric permittivity was changed from 8.6 (neat polyimide) to 5.5 (PI3).
Keywords: Polyimide; POSS; dielectric; nanocomposite